Pengembangan E-Modul Pengelolaan Kearsipan Berbasis Moodle Untuk Meningkatkan Hasil Belajar Siswa Manajemen Perkantoran Dan Layanan Bisnis SMK Swasta Bina Satria Medan - Mutmainnah, Sri; Rozaini, Noni; Suhardini, Atika (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
One of the fields of expertise taught in Vocational High Schools (SMK) under the Office Management and Business Services program is archiving, where students are required to quickly understand the material and effectively perform archival practices. This study aims to develop a Moodle-based e-module, analyze the feasibility of the teaching material through validation assessments from subject matter experts, media experts, and instructional design experts, and examine students' responses through individual trials, small group trials, and large group trials. The study also analyzes students' responses to the developed product, focusing on the archival management subject in the 11th-grade MPLB class. This research adopts the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as a research approach, as proposed by Dick and Carey. The study involves 32 students from class XI IPS 2 as the research subjects. The findings indicate that the Moodle-based e-module is considered feasible, obtaining an average score of 81.77%, classified as highly feasible. Furthermore, the developed e-module is proven to be effective in improving students' learning outcomes, as evidenced by the t-test analysis results, which show a significance value (sig. 2-tailed) of 0.000 < 0.05.